The Routledge Guidebook to Thoreau's Civil disobedience - Taylor, Bob Pepperman., author.
1 online resource (vi, 224 pages)
Keywords: "Since its publication in 1849, Henry David Thoreau's Civil Disobedience has influenced protestors, activists and political thinkers the world over. Including the full text of Thoreau's essay, The Routledge Guidebook to Thoreau's Civil Disobedience explores the context of Thoreau's writing, analyses different interpretations of the text and considers how posthumous edits to Thoreau's work have altered its intended meaning. It introduces the reader to: The context of Thoreau's work and the background to his writing The significance of Thoreau's references and allusions The contemporary reception of Thoreau's essay The ongoing relevance of the work and a discussion of different perspectives on the work Providing a detailed analysis which closely examines Thoreau's original work, this is an essential introduction for students of politics, philosophy and history, and all those seeking a full appreciation Thoreau's classic work"--